Identification of characteristics of foot position and angle during swing phase in fallers using principal component analysis - Inai, Takuma; Kobayashi, Yoshiyuki; Huang, Chenhui; Fujita, Koji; Fujimoto, Masahiro; Nihey, Fumiyuki; Yamamoto, Akiko; Nakajima, Kanako; Nakahara, Kentaro; Kutsuzawa, Gaku; Fukushi, Kenichiro; Kudo, Shoma (Frontiers in Bioengineering and Biotechnology, 2023)
Identifying the characteristics of fallers is important for preventing falls because such events may reduce quality of life. It has been reported that several variables related to foot positions and angles during gait (e.g., sagittal foot angle and minimum toe clearance) differ between fallers and non-fallers. However, examining such representative discrete variables may not be sufficient to detect crucial information, which may be contained in the large portions of unanalyzed data. Therefore, we aimed to identify the comprehensive characteristics of foot position and angle during the swing phase of gait in non-fallers and fallers using principal component analysis (PCA). Thirty non-fallers and 30 fallers were recruited for this study. We performed PCA to reduce the dimensions of foot positions and angles during the swing phase and obtained principal component scores (PCSs) for each principal component vector (PCV), which were then compared between groups. The results revealed that the PCS of PCV3 in fallers was significantly larger than that in non-fallers (p = 0.003, Cohen’s d = 0.80). We reconstructed waveforms of foot positions and angles during the swing phase using PCV3 and our main findings can be summarized as follows. Compared to non-fallers, fallers have a (1) low average foot position in the z axis (i.e., height) during the initial swing phase, (2) small average foot angle in the x axis (i.e., rotation in the sagittal plane) during the initial swing phase, and (3) large variability in foot position in the y axis (i.e., anterior/posterior position) during the initial swing phase. We can conclude that these are characteristics of gait related to fallers. Therefore, our findings may be beneficial for evaluating fall risk during gait using a device such as a shoe- or insole-embedded inertial measurement unit.